Memperluas Dan Meningkatkan Penjualan Pengerajin Perak Di Desa Celuk Gianyar - Putu Pande R. Aprilyani Dewi (CV. ALIM'SPUBLISHING, 2025)
Celuk Village in Gianyar is known as the centre of silver craft with high artistic value, yet local artisans face significant challenges in maintaining sales amidst changing consumption patterns and global competition. This research aims to identify the key constraints faced by Celuk Village's silversmiths, such as limited access to digital marketing technology, lack of product innovation, and lack of understanding of modern business strategies. In addition, local constraints such as reliance on traditional marketing methods and limited training narrow the opportunities for artisans to compete in the global market.The results of the study suggest that the utilisation of digital technology, product design innovation, and improved business management skills can be strategic solutions to expand market reach and improve the competitiveness of Celuk Village's silver crafts. Support in the form of training and facilitating access to e-commerce platforms is also needed to introduce their products to modern consumers without abandoning cultural identity. The findings are expected to contribute to a sustainable silversmith empowerment programme, while supporting the preservation of local cultural heritage in the digital era.